2012
DOI: 10.1002/ijc.27562
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking epidermal PPARγ exhibit a marked augmentation in photocarcinogenesis associated with increased UVB‐induced apoptosis, inflammation and barrier dysfunction

Abstract: Recent studies suggest that peroxisome proliferator-activated receptor gamma (PPARγ) agonists may have cancer chemopreventive activity. Other studies have shown that loss of epidermal PPARγ results in enhanced chemical carcinogenesis in mice via unknown mechanisms. However, ultraviolet B (UVB) exposure represents the primary etiological agent for skin cancer formation and the role of PPARγ in photobiology and photocarcinogenesis is unknown. In previous studies, we demonstrated that UVB irradiation of cells res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 50 publications
(78 reference statements)
3
57
0
Order By: Relevance
“…The augments of UVB-induced Caspase 3/7 activity, apoptosis, and inflammation were extremely more obvious than those in wild type littermates [31]. Consistently, increases in apoptosis and inflammation were performed after blocking the PPAR γ activity by GW9662 treatment [31]. Above research supported our hypothesis that the anti-inflammatory effects of melanogenesis depended on the activation of PPAR γ to trigger the activity of tyrosinase.…”
Section: Discussionsupporting
confidence: 58%
“…The augments of UVB-induced Caspase 3/7 activity, apoptosis, and inflammation were extremely more obvious than those in wild type littermates [31]. Consistently, increases in apoptosis and inflammation were performed after blocking the PPAR γ activity by GW9662 treatment [31]. Above research supported our hypothesis that the anti-inflammatory effects of melanogenesis depended on the activation of PPAR γ to trigger the activity of tyrosinase.…”
Section: Discussionsupporting
confidence: 58%
“…Studies by us and others have shown that this treatment consistently results in initial tumor formation within 11–12 weeks of treatment (19, 20). We therefore discontinued UVB treatments after 10 weeks of treatment.…”
Section: Methodsmentioning
confidence: 87%
“…Examining Hgb content beginning two weeks after cessation of UVB dosing allowed us to examine changes in blood supply at the time when tumors initially begin to appear in this mouse model (19, 20), but after the acute sunburn effect had resolved. This also mimics human behavior, in which sun-avoidance strategies are often employed only after significant cutaneous photodamage is apparent or a first tumor is found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations